2014
DOI: 10.1007/s13524-014-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Women’s Economic and Non-Economic Activities in Minya, Egypt

Abstract: Intimate partner violence (IPV) against women is widespread, but its implications for their economic and non-economic activities are understudied. Leveraging new data from 564 ever-married women aged 22–65 in rural Minya, Egypt, we estimated logistic regressions and zero-inflated negative binomial regressions to test spillover, compensation, and patriarchal bargaining theories about the influences of women's exposure to IPV on their engagement in and time spent on market, subsistence, domestic, and care work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 70 publications
5
21
0
Order By: Relevance
“…This approach corroborates the work of others (e.g. Agarwala and Lynch 2006; Sandberg and Rafail 2013) and our own (Yount et al 2014) using questions on the justification of violence against wives to measure dimensions of women’s agency or related constructs. After removing one item with a significant cross-loading on a second factor (FM_01), we chose a final, 15-item, three-factor model over other factor models based on factor loadings, model fit indices (RMSEA close to 0.060 or less; CFI close to 0.950 or greater; TLI close to 0.950 or greater) (Brown 2006; Harrington 2008), and theoretical interpretation.…”
Section: Methodssupporting
confidence: 83%
“…This approach corroborates the work of others (e.g. Agarwala and Lynch 2006; Sandberg and Rafail 2013) and our own (Yount et al 2014) using questions on the justification of violence against wives to measure dimensions of women’s agency or related constructs. After removing one item with a significant cross-loading on a second factor (FM_01), we chose a final, 15-item, three-factor model over other factor models based on factor loadings, model fit indices (RMSEA close to 0.060 or less; CFI close to 0.950 or greater; TLI close to 0.950 or greater) (Brown 2006; Harrington 2008), and theoretical interpretation.…”
Section: Methodssupporting
confidence: 83%
“…Although some women in our sample did cling to customary feminine roles for women in accordance with notions of latent power, the majority felt that it was important for women to ensure their future security by becoming financially independent from their husbands, as has been found by scholars in contexts such as Arab women in Israel and Egypt (Yount, Zureick-Brown, & Salem, 2014;El Saadawi, 2007;Moghadam, 2013). Women's perspectives on financial independence as necessary suggest that, at least in Qatar, younger women may be changing their views about "good womanhood," and thus, are moving away from adhering to the neo-patriarchal bargain.…”
Section: Williams Et Al 2013)mentioning
confidence: 74%
“…A survey effect based on the difference in sampling methodologies across the two studies is the likely explanation for the discrepancy in reported IPV. General population-based surveys, such as the PNS, show lower reporting of violence as compared to VAW-specific surveys like the WHO MCS [22]. Additionally, the methodological differences between the WHO MCS-Brazil and the PNS, as well as a limited sample size based on gender, contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 99%